PORNOGRAPHIC LANGUAGES ​​IN THE BOOK OF FATH AL-IZAR(A Semiotic and Sexological Approach) - Muhammad Syaiful Bahri Hidayat; Mujibur Rohman, Moh.; Andaryani, Sutinah Andaryani; Nugroho, Agung Yuliyanto Nugroho (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2025)
This article is a research with a literature review or known as library research. Researchers are interested in carrying out a dissection of the editorial language contained in the book Fath al-Izar. The book Fath al-Izar itself is quite famous among Islamic boarding schools and is a book that is considered to ignite enthusiasm and relieve drowsiness. Because in this book there are discussions that are taboo but rich in education, let's call it a sexology book. Namely a book that studies the intimate relationship between a husband and his wife as well as the criteria for choosing a good and cool woman to have a biological relationship with. As a book with sexual overtones, of course the author is interested in studying the pornographic language in the book Fath al-Izar. Research focus: 1) How is the internalization of learning about the book of Fath al-Izar in Islamic boarding schools and its review in the science of sexology? 2) Is it relevant for Islamic boarding schools to teach pornography-based things? and 3) what is the semiotic review of the use of pornographic language contained in the book Fath al-Izar? This research uses two approaches, namely the semiotic approach and the sexology approach. The research results show that Islamic boarding schools implicitly teach sexology through classical fiqh and the book Fath al-Izar is part of it. Sex education that is integrated with Islamic religious values ​​in Islamic boarding schools plays a crucial role in equipping the young Muslim generation with a comprehensive and balanced understanding of sexuality. From a semiotic perspective, the pornographic language contained in the book of Fath al-Izar is quite clear and makes for a wider reinterpretation for readers or students.